Construction of stability domains for linear differential-difference equations - Klevchuk, I.I.; Pernay, S.A.; Cherevko, I.M. (National Academy of Sciences of Ukraine, 2012)
We investigate the boundedness conditions and the methods of construction of a stability domain of linear differential equations with several delays.
We investigate the boundedness conditions and the methods of construction of a stability domain of linear differential equations with several delays.
Keywords: delay differential equation, stability domain, argument principle, D-partition